SENP3 loss promotes M2 macrophage polarization and breast cancer progression. Issue 4 (29th May 2021) - Xiao, Ming; Bian, Qi; Lao, Yimin; Yi, Jing; Sun, Xueqing; Sun, Xuxu; Yang, Jie
Abstract : Tumor‐associated macrophages (TAM) play a crucial role in promoting cancer progression. Upon cytokine stimulation, TAM preferentially polarize to the anti‐inflammatory and pro‐tumor M2 subtype. The mechanism underlying such preferential polarization remains elusive. Here, we report that macrophage‐specific deletion of the SUMO‐specific protease Sentrin/SUMO‐specific protease 3 promotes macrophage polarization towards M2 in bone marrow‐derived macrophage (BMDM) induced by interleukin 4 (IL‐4)/IL‐13 and in an ex vivo model (murine Py8119 cell line), as well as in a mouse orthotopic tumor model. Notably, Sentrin/SUMO‐specific protease 3 (SENP3) loss in macrophages accelerated breast cancer malignancy in ex vivo and in vivo models. Mechanistically, we identified Akt Serine/threonine kinase 1 (Akt1) as the substrate of SENP3 and found that the enhanced Akt1 SUMOylation upon SENP3 loss resulted in Akt1 hyper‐phosphorylation and activation, which facilitates M2 polarization. Analysis of clinical data showed that a lower level of SENP3 in TAM has a strong negative correlation with the level of the M2 marker CD206, as well as with a worse clinical outcome. Thus, increased Akt1 SUMOylation as a result of SENP3 deficiency modulates polarization of macrophages to the M2 subtype within a breast cancer microenvironment, which in turn promotes tumor progression. Abstract : Cytokine induced polarization of tumor‐associated macrophages are crucial for cancer progression. Here we investigated the role of SUMO specific peptidase 3 (SENP3) in macrophage polarization. Loss of SENP3 resulted in SUMOylation and hyper‐phosphorylation of Akt1 that in turn facilitated M2 polarization by the cytokines like IL‐4. Altogether, loss of SENP3 contributed to tumor progression and worse prognosis in patients with breast cancer. ​